Community Empowerment Through Integrated Cattle Farming in Muara Satu District, Lhokseumawe City, Aceh Province - Ramli, Armia; Ramadhani, Sri Indah; Harahap, Reiki Nauli; Nasruddin, Nasruddin; Khusrizal, Khusrizal; Nazaruddin, M; Putranto, Nurseno Dwi (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Community empowerment is the responsibility of all parties as mandated by the law. The private sector must do some programs that benefit and positively impact all its surroundings. PT Pertamina Hulu Energi (PHE) North Sumatra Offshore (NSO), which operates in Aceh, has done a Corporate Social Responsibility (CSR) program by empowering the community through integrated cattle farming in Muara Satu District, Lhokseumawe City, Aceh Province. This program will be carried out by assisting with as many as twenty-two cattle and assistance to farmers for five months in 2022. Cattle assistance was provided for eleven Gampong (villages) through the Forum Geuchik (village heads) of Muara Satu District, Lhokseumawe City. This program is well implemented, marked by success in fattening and profits between Rp2.500.000 to Rp4.000.000 per head of cattle within five months of rearing. Integrated livestock can develop into a Village Owned Enterprise (BUMDes). This program allows for replication to various areas around the community development area by PT Pertamina Hulu Energi (NSO)